2012
DOI: 10.1016/j.jprocont.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Model-based temperature control of a diesel oxidation catalyst

Abstract: To cite this version:Olivier Lepreux. Model-based Temperature Control of a Diesel Oxidation Catalyst . Mathematics T H E S E pour obtenir le grade de DOCTEUR DE L'ECOLE NATIONALE SUPERIEURE DES MINES DE PARIS RésuméLe problème étudié dans cette thèse est la commande d'un système DOC (Diesel Oxidation Catalyst) tel qu'utilisé dans les systèmes de dépollution des gaz d'échappement des moteurs Diesel automobiles.Ce système est par nature un système à paramètres répartis en raison de sa géométrie allongée parcou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…On the contrary, increasing CO concentration from 530 ppm to 5780 ppm and flow rate from 24 kg/hr to 93 kg/hr will decrease CO conversion efficiency from 50% to 25%. Trends from these experiments are found to be consistent to the literature found in [5], [7], and [12]. Results from above figures have shown that these 4 factors -exhaust temperature, exhaust flow rate, CO and O2 concentration affect CO conversion efficiency.…”
Section: Fractional Factorial Designsupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, increasing CO concentration from 530 ppm to 5780 ppm and flow rate from 24 kg/hr to 93 kg/hr will decrease CO conversion efficiency from 50% to 25%. Trends from these experiments are found to be consistent to the literature found in [5], [7], and [12]. Results from above figures have shown that these 4 factors -exhaust temperature, exhaust flow rate, CO and O2 concentration affect CO conversion efficiency.…”
Section: Fractional Factorial Designsupporting
confidence: 87%
“…High O2 concentration will increase the efficiency, while high CO concentration will decrease the efficiency [6]. At higher exhaust temperature, pre-CAT temperature, CO will decrease with better efficiency [7]. And lastly, the exhaust flow rate in which lower flow rate leads better efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Following along a study in [14], it can be verified that the reduced model is equivalent, at constant speed v(t) = v and at order 0 in ε = v/k 1 , with…”
Section: Appendix A: Explanation Of Overshoot On a Simple Model A Simmentioning
confidence: 87%
“…This model, actually deduced from the reduced model [14], allows to describe the overshoot phenomena in its simplest form. The analytical study of this model gives the formal expression of the output response to a step change in L c (t), for an arbitrary trajectory, related to the actual control and forced to be uniform over the length L c (t).…”
Section: Compensation Of Overshoot Phenomenonmentioning
confidence: 99%
“…In this paper, following the overture presented in [12], we propose to represent the chemical reactions inside the catalyst as a temperature entering the system at a virtual entry point located downstream of the physical inlet of the monolith. To make this approach compliant with SI engines applications, it is proposed here to use the catalyst efficiency conversion to calculate the gain relating the heat release to the fictitious temperature.…”
Section: Introductionmentioning
confidence: 99%